Quality of aged shoulder from lambs fed with different oldman saltbush hay levels (Atriplex nummularia) - Alvarenga, Tharcilla Isabella Rodrigues Costa (2014)
This study assessed the effects of different levels of oldman saltbush hay and ageing time on the physical characteristics of Santa Inês lamb meat. Sixty shoulders from 32 male lambs fed with 30, 40, 50 or 60% oldman saltbush hay for 60 days were vacuum-packaged and stored in a refrigerator at 0 ± 1°C for 0, 7 or 14 days of ageing. The shear force, cooking loss and water holding capacity were 3.06kgf cm-2, 37.28% and 76.71%, respectively, and there were no significant changed by studied factors (P>0.05)